2021
DOI: 10.1177/08862605211015213
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and its Mental Health Implications Amid COVID-19 Lockdown: Findings Among Nigerian Couples

Abstract: Intimate partner violence (IPV) has been identified as a global health problem with increasing mental health consequences. During the COVID-19 pandemic lockdown in Nigeria, couples were compelled to spend more time together, regardless of their pre-existing challenges. Our study aims to determine the prevalence of IPV, its forms, and mental health implications among Nigerian households amid the COVID-19 lockdown. A cross-sectional study was implemented which used the snowball sampling technique to recruit 474 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Some studies suggest increased intimate partner violence during COVID-19 measures, 21,22 while others found decreases. 23 Other research has shown that IPV may increase after a natural disaster, 24 indicating a need for follow up studies to see if IPV worsened as the COVID-19 pandemic continued beyond the initial wave that we examined in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Some studies suggest increased intimate partner violence during COVID-19 measures, 21,22 while others found decreases. 23 Other research has shown that IPV may increase after a natural disaster, 24 indicating a need for follow up studies to see if IPV worsened as the COVID-19 pandemic continued beyond the initial wave that we examined in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Further studies in this review were conducted in Austria, the Czech Republic, Egypt, Ethiopia, Iraq, Jordan, Nigeria, Peru, Saudi Arabia, Switzerland, and Tunisia. Ten studies included only females ( 37 , 41 43 , 46 49 , 51 , 54 ), 10 further studies included both female and male participants ( 13 , 39 , 44 , 45 , 50 , 52 , 53 , 55 57 ), and two studies assessed DV in males only ( 38 , 40 ). Without exception, all studies reported on DV against adults, with only one study further reporting on violence against children ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the n = 19 cross-sectional studies assessed different types of DV. To this end, 12 studies reported on changes in psychological/emotional or verbal DV ( 13 , 37 40 , 42 , 45 , 46 , 48 50 , 53 ), 11 on sexual DV ( 13 , 37 39 , 42 , 45 , 46 , 48 50 , 53 ), 12 reported on physical DV ( 13 , 37 39 , 42 , 45 , 46 , 48 50 , 52 , 53 ), and 4 included economic/financial DV ( 39 , 49 , 50 , 53 ). One study did not provide a differentiation of DV type ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women of Pakistan are facing domestic violence increasingly when compared to other countries; family violence in New Zealand was reported to be 4 times lesser (9%) ( Every-Palmer et al, 2020 ) while that in Nigeria was also 3–4 times less (7.5–13.5%) ( Ojeahere et al, 2021 ). The disparity in the cases of family violence reported in Pakistan and elsewhere is possibly due to the prevailing socio-cultural norms in Pakistan.…”
Section: Discussionmentioning
confidence: 99%